Recent advances in polymer supporting layered double hydroxides nanocomposite for electrochemical biosensors. (23rd January 2018) - Dhanasekaran, T; Padmanaban, A; Gnanamoorthy, G; Manigandan, R; Kumar, S Praveen; Stephen, A; Narayanan, V
Abstract: In recent years, layered double hydroxides (LDHs) materials having emerging due to their ability of intercalate a variety of anions, either organic or inorganic molecules. The most significance of the LDHs has been found potential applications in catalysis, wastewater treatment, and electrochemical sensors. The Mg–Al LDHs (MAL) and Poly-o-phenylenediamine @ Mg–Al LDHs (P-MAL) was prepared via simple one step hydrothermal method. As prepared material was characterized using many techniques such as, the structural and crystal phase was determined from XRD and Raman analyses. The functional groups were depicted using FT-IR spectroscopy. The optical propertied studied using diffuse reflectance spectroscopy UV–vis spectroscopy and the emission property were analyzed from Photoluminescence spectroscopy. The surface morphology and average particle size was analyzed using FESEM microscopy. The prepared polymer composite material P-MAL was further used for highly sensitive electrochemical detection towards dopamine (DA).